Brachytherapy in treatment of vaginal cancer - A. D. Kaprin; V. N. Galkin; S. A. Ivanov; V. A. Solodkiy; V. A. Titova (Biomedical Photonics, 2016)
Characteristics of diagnosis and treatment of different types of primary vaginal cancer are highlighted, the role and place of brachytherapy as independent method or combined treatment modality for this pathology is shown in the review. Epidemiological data on incidence of vaginal cancer in Russia are represented, presumptive mechanisms for development of the disease, risk factors, histological types, features of the course, clinical presentation, diagnostic algorithm are described. Treatment methods for primary vaginal cancer according to world standards such as surgery, radiotherapy and systemic drug therapy are covered. Specifics of radiological methods of treatment (low-dose rate and high-dose rate brachytherapy, including the combination with external beam radiotherapy) according to the stage of the disease, are shown in details. The results of several large foreign clinical trials for efficiency of different methods of radiotherapy are discussed. The combination of brachytherapy on primary tumor with external radiation therapy to the lymph nodes was confirmed to be the most effective modality. The conclusion on opportunities of different methods of radiotherapy in treatment of vaginal cancer was made.